Answers

2015-07-15T14:31:45+08:00
Factoring the Polynomials is not same as factoring other numbers. When factoring polynomials, you are finding polynomials that can be divide from the original numbers/polynomials.


Like this:

2 (x+3) = 2 (x) + 2 (3) = 2x+6

2x+6 = 2 (x) + 2 (3) = 2 (x+3)



Example:


Factor the 3x-12.

~ I'll factor this number:


3x-12 = 3 (     )

~ Divide the "3" out of "3x", there was only left, only the "x" is remaining. Afterwards, put "x" inside of the parenthesis.


3x-12 = 3 (x    )

~ Divide 3 out of "-12", the left was "-4" put it again inside of the parenthesis.


3x-12 = 3 (x - 4)



And the final answer is... 3 (x - 4)



========================================================

I know that I didn't explain it well, but I hope at least it help to you. ^^
0